2023
DOI: 10.3390/ma16051830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of K2TiF6 and Electrolyte Temperatures on Energy Consumption and Properties of MAO Coatings on 6063 Aluminum Alloy

Abstract: To decrease energy consumption and improve the performance of micro-arc oxidation (MAO) films on 6063 Al alloy, a policy of K2TiF6 additive and electrolyte temperature control was adapted. The specific energy consumption relied on the K2TiF6 additive and more particularly on the electrolyte temperatures. Scanning electron microscopy demonstrates that electrolytes with 5 g/L K2TiF6 can effectively seal the surface pores and increase the thickness of the compact inner layer. Spectral analysis shows that the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Literature review shows that PEO Al 2 O 3 -ZrO 2 coating may be produced through addition of ZrO 2 nanoparticles [2], or Zr-based salt additives such as potassium zirconium carbonate (K 2 [Zr(CO 3 ) 2 (OH) 2 ]) [14], and dipotassium hexafluorozirconate (K 2 ZrF 6 ) [7,15] into the electrolytic solution. Matykina et al [2] prepared this coating in phosphate-based and silicate-based electrolytes, which contain monoclinic ZrO 2 nano particles (m-ZrO 2 ), and observed that the phosphate-based electrolytic solution developed high-temperature forms of zirconia including tetragonal ZrO 2 (t-ZrO 2 ) and/or cubic ZrO 2 (c-ZrO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review shows that PEO Al 2 O 3 -ZrO 2 coating may be produced through addition of ZrO 2 nanoparticles [2], or Zr-based salt additives such as potassium zirconium carbonate (K 2 [Zr(CO 3 ) 2 (OH) 2 ]) [14], and dipotassium hexafluorozirconate (K 2 ZrF 6 ) [7,15] into the electrolytic solution. Matykina et al [2] prepared this coating in phosphate-based and silicate-based electrolytes, which contain monoclinic ZrO 2 nano particles (m-ZrO 2 ), and observed that the phosphate-based electrolytic solution developed high-temperature forms of zirconia including tetragonal ZrO 2 (t-ZrO 2 ) and/or cubic ZrO 2 (c-ZrO 2 ).…”
Section: Introductionmentioning
confidence: 99%